2006
DOI: 10.1038/sj.emboj.7601417
|View full text |Cite
|
Sign up to set email alerts
|

TRPC3 and TRPC6 are essential for angiotensin II-induced cardiac hypertrophy

Abstract: Angiotensin (Ang) II participates in the pathogenesis of heart failure through induction of cardiac hypertrophy. Ang II-induced hypertrophic growth of cardiomyocytes is mediated by nuclear factor of activated T cells (NFAT), a Ca 2 þ -responsive transcriptional factor. It is believed that phospholipase C (PLC)-mediated production of inositol-1,4,5-trisphosphate (IP 3 ) is responsible for Ca 2 þ increase that is necessary for NFAT activation. However, we demonstrate that PLC-mediated production of diacylglycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
331
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(347 citation statements)
references
References 49 publications
15
331
1
Order By: Relevance
“…Simple overexpression of TRPC3 or TRPC6 in the mouse heart was sufficient to induce Ca 2+ entry and enhance the cardiac hypertrophic response (4,5). Mechanistically, we and others have shown that TRPC channels engage calcineurin-NFAT signaling in the heart, a well-known prohypertrophic pathway that is both necessary and sufficient for growth (4)(5)(6)(7). Indeed, deletion of calcineurin Aβ reduced hypertrophic inducibility by TRPC3 overexpression in the heart (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simple overexpression of TRPC3 or TRPC6 in the mouse heart was sufficient to induce Ca 2+ entry and enhance the cardiac hypertrophic response (4,5). Mechanistically, we and others have shown that TRPC channels engage calcineurin-NFAT signaling in the heart, a well-known prohypertrophic pathway that is both necessary and sufficient for growth (4)(5)(6)(7). Indeed, deletion of calcineurin Aβ reduced hypertrophic inducibility by TRPC3 overexpression in the heart (5).…”
Section: Discussionmentioning
confidence: 99%
“…More provocatively, TRPC channels probably coexist with TRPM and TRPP subclasses of channels in even larger channel complexes (16,17). Because all TRPC family members have been detected in the heart, some of which are up-regulated by hypertrophy (4)(5)(6)(7)23), it is likely that many combinations of tetramers are possible and can generate unique cation influx properties. However, combined inhibition of both subfamilies in dnTRPC4, dnTRPC3 DTG mice completely eliminated all TAC-associated Ca 2+ entry, suggesting that not all TRPC complexes show crossoligomerization in the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakayama et al (71) showed that calcineurin/NFAT-mediated signaling and hypertrophy were dependent on TRPC4. In addition, TRPC3 and TRPC6 have also been shown to contribute to the development of ANG II-induced hypertrophy (79), and SOCE and NFAT translocation have been shown to be increased in HEK293 cells overexpressing TRPC1 (78). Interestingly, as recently as 2011, although describing the significance of SOCE in cardiomyocytes as a mystery, Eder and Molkentin nevertheless concluded that "TRPC channels are bona fide regulators of cardiac hypertrophy associated with pathological events and neuroendocrine signaling" (18).…”
Section: Orai1/trpcmentioning
confidence: 99%
“…Expression level of AT 1 R in rat neonatal cardiac fibroblasts is more than fivefold higher than that in rat neonatal cardiomyocytes (65 ± 12 fmol/mg protein), and AT 1 R signaling in cardiac fibroblasts has been implicated in the development of cardiac fibrosis (17). We have previously reported that treatment with Ang II increases activity of nuclear factor of activated T cells (NFAT), a Ca 2+ -dependent transcriptional factor that is predominantly regulated by calcineurin, both in cardiac myocytes and fibroblasts (18,19). Activation of NFAT has been implicated in the development of cardiac hypertrophy (20), but the role of NFAT in cardiac fibroblasts is not fully known.…”
mentioning
confidence: 99%